Quality of Life, Lifestyle Behaviors, and Well-Being in Patients With Cancer: The Impact of Demographic Variables - Ioannis, Paxinos; Michel, Ammari (British Journal of Healthcare and Medical Research, 2022)
Background: Cancer can challenge all aspects of a person’s quality of life (QoL) and well-being, including physical, psychological, social and spiritual. QoL has long been a central question in cancer research. Optimal QoL has become a goal in health care. It can be argued that the improvement of QoL should be a primary goal of cancer care. Lifestyle factors have been repeatedly identified as cancer risk factors. Unhealthy lifestyle behaviors are associated with serious illnesses such as cancer. How lifestyle behaviors affect the cancer control continuum have not been well-studied. Objective: This study evaluates the relation between lifestyle behaviors, perceived quality of life, well-being and tries to expand knowledge regarding the correlation between them. Methodology: 105 oncology outpatients who have been submitted in pain therapy in the Pain Unit of an Ongological Hospital in Greece in 2021, were administrated the World Health Organization OoL instrument (WHOQOL-BREF) the WHO (10 items) Well-Being Index and an improvised questionnaire with Lifestyle indices. The present study is a cross-sectional, descriptive, correlational research design. Results: This study suggests that male patients’ well-being scores were significantly higher. The patients also reported higher scores in the psychological and environmental domain of QoL but they scored significantly lower in the dimensions of physical health, smoking and alcohol use of Lifestyle. Older cancer patients reported lower levels on the well-being and also lower scores on the QoL in the physical, psychological and social relationships domains. They also reported less on the lifestyle variables, particularly on physical health(p=>.05),food consumption(p=>.05), observing weight control (p=.04)and exercise and well-being(p=0.02). More educated patients reported significantly higher scores in the psychological and environment domains of QoL and presented a significantly higher scores in physical health, smoking and alcohol use of lifestyle indices indicating more healthy lifestyle patterns. Conclusions: Findings provide evidence that demographic variables such as being male, younger more educated relate to a more preserved QoL. Regarding lifestyle patterns being female, younger and more educated relate to a more healthy behaviors.